2018
DOI: 10.1016/j.copbio.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Engineering microbial fatty acid metabolism for biofuels and biochemicals

Abstract: Traditional oleochemical industry chemically processes animal fats and plant oils to produce detergents, lubricants, biodiesel, plastics, coatings, and other products. Biotechnology offers an alternative process, where the same oleochemicals can be produced from abundant biomass feedstocks using microbial catalysis. This review summarizes the recent advances in the engineering of microbial metabolism for production of fatty acid-derived products. We highlight the efforts in engineering the central carbon metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
91
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 49 publications
0
91
0
Order By: Relevance
“…Genetic studies of R. toruloides have shown that its lipid accumulation capacity can be further enhanced (reviewed in (Marella, Holkenbrink, Siewers, & Borodina, 2018)). We employed Flux Scanning based on Enforced Objective Function (FSEOF) on rhto-GEM to identify potential metabolic engineering targets for improved production of TAG.…”
Section: Prediction Of Potential Targets For Increased Production Of mentioning
confidence: 99%
“…Genetic studies of R. toruloides have shown that its lipid accumulation capacity can be further enhanced (reviewed in (Marella, Holkenbrink, Siewers, & Borodina, 2018)). We employed Flux Scanning based on Enforced Objective Function (FSEOF) on rhto-GEM to identify potential metabolic engineering targets for improved production of TAG.…”
Section: Prediction Of Potential Targets For Increased Production Of mentioning
confidence: 99%
“…In this sense, central carbon metabolism, cofactor balance, regulation, and metabolite transport should be optimized. Current strategies to improve lipid production include increasing the supply of lipid precursors and/or avoiding lipid degradation together with the overcoming of limiting factors(Marella, Holkenbrink, Siewers, & Borodina, 2018; González-Fernández and Muñoz, 2017).…”
mentioning
confidence: 99%
“…[1][2][3] Ac lear structural understanding of ACPs and their interactions with partner enzymes is essential to furthering metabolic engineering and drug discovery.E fforts in this regard have proven challenging due to transient interactions and the dynamic nature of the ACP, which transports intermediates to multiple enzymes via ac ovalent but labile thioester linkage.T he archetypical carrier protein AcpP,w hich is involved in type II fatty acid biosynthesis in Escherichia coli,h as been well studied, [4,5] but key questions regarding conformational dynamics and interactions between AcpP and partner enzymes remain partially understood. We explored the importance of the thioester bond to the structure of the carrier protein by using solution NMR spectroscopya nd molecular dynamics simulations.Remarkably,the replacement of sulfur with other heteroatoms results in significant structural changes,t hus suggesting more rigorous selections of isosteric substitutes is needed.…”
mentioning
confidence: 99%
“…[1][2][3] Ac lear structural understanding of ACPs and their interactions with partner enzymes is essential to furthering metabolic engineering and drug discovery.E fforts in this regard have proven challenging due to transient interactions and the dynamic nature of the ACP, which transports intermediates to multiple enzymes via ac ovalent but labile thioester linkage.T he archetypical carrier protein AcpP,w hich is involved in type II fatty acid biosynthesis in Escherichia coli,h as been well studied, [4,5] but key questions regarding conformational dynamics and interactions between AcpP and partner enzymes remain partially understood. [1][2][3] Ac lear structural understanding of ACPs and their interactions with partner enzymes is essential to furthering metabolic engineering and drug discovery.E fforts in this regard have proven challenging due to transient interactions and the dynamic nature of the ACP, which transports intermediates to multiple enzymes via ac ovalent but labile thioester linkage.T he archetypical carrier protein AcpP,w hich is involved in type II fatty acid biosynthesis in Escherichia coli,h as been well studied, [4,5] but key questions regarding conformational dynamics and interactions between AcpP and partner enzymes remain partially understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation